The Relationship between Grades 8-12 Students’ Motivation for Self-Selected Reading in English and Academic Achievement at Bangkok Christian International School, Thailand - Lungley, Martin; Lynch, Richard (Scholar: Human Sciences, 2018)
The purpose of this study was to determine the extent to which academic achievement is influenced by motivation for self-selected reading in English and reading achievement. This study was conducted using the survey method employing the researcher made Adolescent Motivation for Self-Selected Reading Questionnaire (AMSSRQ). Academic achievement data was collected from students’ individual report cards for the first quarter of the academic year 2015-16. The sample of the study consisted of 83 eighth to twelfth grade students from Bangkok Christian International School, Bangkok, Thailand, in the first semester of the academic year 2015-16. Additionally, the relationship between motivation for self-selected reading in English and reading achievement, and reading achievement and academic achievement were investigated. Further to this the relationship between motivations for self-selected reading in English and general self-efficacy for learning and performance were also investigated. The hypotheses were tested using the Pearson product-moment correlation coefficient. The results confirmed the hypotheses. There was a significant relationship between motivation for self-selected reading in English and reading achievement. In turn there was a significant relationship between reading achievement and academic achievement. Additionally, this study found a significant relationship between motivation for self-selected reading in English and general self-efficacy for learning and performance. The study concludes with recommendations for practice and future research.